2013
DOI: 10.1186/scrt350
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the viability of human mesenchymal stem cells

Abstract: IntroductionImpaction allograft with cement is a common technique used in revision hip surgeries for the last 20 years. However, its clinical results are inconsistent. Recent studies have shown that mesenchymal stem cells (MSCs) seeded onto allograft can enhance bone formation. This in vitro study investigates whether the increase in temperature related to the polymerisation of bone cement will affect the viability of human MSCs.MethodsThe viability of human MSCs was measured after incubating them at temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Following an additional incubation of 48 hours, its therapeutic efficacy was evaluated. Importantly, our first observation was that mild magnetic hyperthermia alone did not significantly affect AD-MSC viability, which agrees with previously published results on the effects of heat on stem cell viability (Figure 6C) [44]. In terms of its therapeutic efficacy, A2780 ovarian cancer cells treated with conditioned media from the engineered AD-MSCs that were exposed to mild magnetic hyperthermia showed a remarkable decrease in cell viability (40% decrease) when compared to those treated with conditioned media from engineered AD-MSCs controls that had not been exposed to mild magnetic hyperthermia (Figure 6D).…”
Section: Resultssupporting
confidence: 92%
“…Following an additional incubation of 48 hours, its therapeutic efficacy was evaluated. Importantly, our first observation was that mild magnetic hyperthermia alone did not significantly affect AD-MSC viability, which agrees with previously published results on the effects of heat on stem cell viability (Figure 6C) [44]. In terms of its therapeutic efficacy, A2780 ovarian cancer cells treated with conditioned media from the engineered AD-MSCs that were exposed to mild magnetic hyperthermia showed a remarkable decrease in cell viability (40% decrease) when compared to those treated with conditioned media from engineered AD-MSCs controls that had not been exposed to mild magnetic hyperthermia (Figure 6D).…”
Section: Resultssupporting
confidence: 92%
“…At 12 and 24 h, H2 had significantly higher cell viability, while H5 showed significant lower cell viability compared with NC. This reduced cell viability as temperature increased temperate is in agreement with a previous study on the effect of heat stress on avian cells (Harding et al, 2016), human mesenchymal stromal cells (Reissis et al, 2013), mammalian epithelial cells (Du et al, 2008), and fish hepatic cells (Cui et al, 2013). Our results showed that like viability, the proliferation of CEF was also decreased when cells were maintained at high temperature for 24 h. Higher CEF proliferation was observed in the experimental groups H1, H2, H3, and H4 at 6 and 12 h. The results presented in this study provide the evidence of the beneficial effects of mild heat shock for a short duration on the viability and proliferation of CEF.…”
Section: The Effect Of High Temperature On Viability Proliferation supporting
confidence: 93%
“…Cell viability was assessed by trypan blue exclusion method as described previously (Reissis et al., ). No cell death was observed for different concentrations of SPD‐MAA over a period of 6 to 48 hours.…”
Section: Resultsmentioning
confidence: 99%